E. coli biotype 1 and E. coli O157:H7 determination in cattle carcasses at processing plants in the department of Atlántico (Colombia) - Rosado-Porto, David (2021)
Carcass contamination with E. coli O157:H7, the etiological agent of Acute Diarrheal Disease (ADD) during slaughter is the primary route for contamination of minced beef. The aim of this study was to determine the prevalence of generic E. coli biotype 1 and E. coli O157:H7 in cattle slaughtered in processing plants in the department of Atlántico. In total, 224 bovine carcasses from processing plants in four municipalities were analyzed. The samples were processed in the Public Health Laboratory of the department of Atlántico. E. coli O157:H7 were determined by the VIDAS UP method, E. coli O157 (including H7) (ECPT) and biotype 1 E. coli using TBX agar (Oxoid), ISO 16649-2: 2000 method. The prevalence of E. coli O157:H7 was 0.45% and of generic E. coli biotype 1 was 0.89% in samples with E. coli biotype 1 counts >100 CFU/cm2. In 54% of the carcasses with the presence of E. coli, the concentrations ranged between 1 and 758 CFU/cm2. It is concluded that the prevalence of E. coli O157:H7 found was low (0.45%); however, it indicates the presence of this pathogenic strain in the area, therefore, it is necessary to strengthen the surveillance for outlets and distributors.